Responding to pandemic influenza - Van-Tam, Jonathan; Sellwood, Chloe (Henry Stewart Talks, 2014)
Healthcare and societal impacts of a pandemic, Pandemic preparedness, Surveillance and monitoring of a pandemic, Public health countermeasures, Antiviral drugs (influenza), Pandemic influenza vaccines, Healthcare capacity and capability, Pandemic communications, Bioethical issues, Training and exercising